The Chloroplast Genome of the Green Alga Schizomeris leibleinii (Chlorophyceae) Provides Evidence for Bidirectional DNA Replication from a Single Origin in the Chaetophorales - Brouard, Jean-Simon (Oxford University Press, 2011)
In the Chlorophyceae, the chloroplast genome is extraordinarily fluid in architecture and displays unique features relative to other groups of green algae. For the Chaetophorales, 1 of the 5 major lineages of the Chlorophyceae, it has been shown that the distinctive architecture of the 223,902-bp genome of Stigeoclonium helveticum is consistent with bidirectional DNA replication from a single origin. Here, we report the 182,759-bp chloroplast genome sequence of Schizomeris leibleinii, a member of the earliest diverging lineage of the Chaetophorales. Like its Stigeoclonium homolog, the Schizomeris genome lacks a large inverted repeat encoding the rRNA operon and displays a striking bias in coding regions that is associated with a bias in base composition along each strand. Our results support the notion that these two chaetophoralean genomes replicate bidirectionally from a putative origin located in the vicinity of the small subunit ribosomal RNA gene. Their shared structural characteristics were most probably inherited from the common ancestor of all chaetophoralean algae. Short dispersed repeats account for most of the 41-kb size variation between the Schizomeris and Stigeoclonium genomes, and there is no indication that homologous recombination between these repeated elements led to the observed gene rearrangements. A comparison of the extent of variation sustained by the Stigeoclonium and Schizomeris chloroplast DNAs (cpDNAs) with that observed for the cpDNAs of the chlamydomonadalean Chlamydomonas and Volvox suggests that gene rearrangements as well as changes in the abundance of intergenic and intron sequences occurred at a slower pace in the Chaetophorales than in the Chlamydomonadales.